Liturgi yang Profetis: Hubungan Kenabian dan Kultus - Martasudjita, E. Pranawa Dhatu (Jurnal Orientasi Baru, 2012)
Prophecy and liturgy is not a common topic to talk. In general, prophecy is often confronted to liturgy, as many shown in the Old Testament where lots of prophets criticized the Jewish that were strongly hold their devotion and worship to God, but surprisingly their life was much far away from justice and truth. In the context of church life nowadays, a topic about prophecy and liturgy may be focused on the discussion related to prophetic liturgy. Is it possible that liturgy has a characteristic of prophetic? This writing is a research study to find the meaning and possibilities of prophetic liturgy. Throughout qualitative study and liturgy significance intensifying as the unity with God, we could analyze and explore the deepest relationship between liturgy and prophecy. By deepening a prophet’s role and how a prophet catch God’s will, this writing offers three dimensions of prophetic liturgy. The prophetic meaning and characteristic of the liturgy is demanded by the very nature of the liturgy itself.